The South African Reserve Bank’s mandate to promote and maintain financial stability in terms of the Financial Sector Regulation Act 9 of 2017 - Nyaude, Ashley (University of Pretoria, 2025)
Mini-dissertation (LLM (Mercantile Law))--University of Pretoria, 2024.